2011
DOI: 10.1021/bi2000966
|View full text |Cite
|
Sign up to set email alerts
|

Rational Approach To Select Small Peptide Molecular Probes Labeled with Fluorescent Cyanine Dyes for in Vivo Optical Imaging

Abstract: We demonstrate that the structure of carbocyanine dyes, which are commonly used to label small peptides for molecular imaging, and not the bound peptide, controls the rate of extravasation from blood vessels to tissue. By examining several near-infrared (NIR) carbocyanine fluorophores, we demonstrate a quantitative correlation between the binding of a dye to albumin, a model plasma protein, and the rate of extravasation of the probe into tissue. Binding of the dyes was measured by fluorescence quenching of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 41 publications
10
89
1
Order By: Relevance
“…When BSA/ICG = 3, nearly all ICG molecules are bound to BSA and fluorescence starts to saturate. Our fluorescence results not only correlate well with our laser experiments, but also are consistent with a recent finding that a BSA molecule can bind at most one ICG molecule at a time [35,36]. Note that the slight reduction in fluorescence (and hence increase in the ICG lasing threshold) when an excessive amount of BSA was added may be attributed to the additional absorption and scattering loss from BSA.…”
Section: Icg Lasing With Serological Componentssupporting
confidence: 92%
See 1 more Smart Citation
“…When BSA/ICG = 3, nearly all ICG molecules are bound to BSA and fluorescence starts to saturate. Our fluorescence results not only correlate well with our laser experiments, but also are consistent with a recent finding that a BSA molecule can bind at most one ICG molecule at a time [35,36]. Note that the slight reduction in fluorescence (and hence increase in the ICG lasing threshold) when an excessive amount of BSA was added may be attributed to the additional absorption and scattering loss from BSA.…”
Section: Icg Lasing With Serological Componentssupporting
confidence: 92%
“…S4). The slightly lower lasing threshold for HSA than for the BSA counterpart (2.3 μJ/mm 2 ) is due to the relatively high binding affinity of ICG to HSA [35] (hence the ICG quantum yield) as well as the red-shifted fluorescence (and the gain) spectrum (see Fig. S2).…”
Section: Icg Lasing With Serological Componentsmentioning
confidence: 99%
“…[8] In line with this, different cyanine dyes have been selected to control the rate of extravasation of targeting peptides from blood vessels into tissue by their affinity for HSA. [9]…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that LMW fluorescent tracers that have a high affinity to serum proteins and can emit strong fluorescence in the presence of serum proteins are advantageous for CBV imaging because these tracers are unlikely to extravasate from intact BBB and are able to provide the high-contrast fluorescent imaging of CBV. 23 We first measured the fluorescence properties of EB and ICG (Supporting Information Figure 1A and D) in the absence or presence of BSA (Supporting Information Figure 1B and E). The maximum fluorescence intensity (FI max) of EB in the absence and presence of BSA was 6 and 1112, respectively ( Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%